Spatiotemporal patterns and regional disparities in the coupling and coordination between green finance and ecological environment in China - Liu, Zebin; Xiang, Wei; Wang, Jingjing; Chen, Wanxue; Zhou, Yi (Frontiers in Environmental Science, 2025)
Existing studies predominantly explore the link between green finance and ecological environment but overlook their dynamic spatiotemporal evolution and regional disparities. This study optimizes the coupling coordination degree (CCD) model and employs methods such as the Dagum This study innovates by optimizing the CCD model and integrating spatial econometrics with dynamic distribution methodologies to measure the coupling coordination dynamics in China from 2013 to 2022. Findings reveal an overall upward trend but significant regional disparities. The Eastern region exhibits a “high-high” clustering effect, while the Central and Western regions face a “low-low” lock-in, reflecting a “Matthew effect.” Green innovation and environmental governance improve coordination level, whereas resource consumption hinders it, with varying regional impacts. These insights inform targeted strategies, emphasizing regional cooperation and innovation-driven policies for balanced development.